Effects of digital storytelling on young learners' listening comprehension at a primary school - Đoàn, Thị Trúc Linh (Trường Đại học Trà Vinh; Trà Vinh, 2024)
This study aims to investigate how DST courses can impact the listening skills and attitudes of young learners in the Mekong Delta region of Vietnam. We are particularly interested in understanding how young learners perceive the enhancement of their English listening skills through DST.